Improving Birth Registration Using the Health System: A Case Study from Somali Region of Ethiopia - , Oladeji Olusola, Abdifatah Elmi Farah, Bukhari Sheik Aden, Anjola Oladeji, Adam Issack, Juweria Mohamed, Ann Robins, Mohamed Elabe, Abdifatah Ali Mohammed (Archives of Current Research International, 2022)
Birth registration is the process by which the event and characteristics of a child’s birth are recorded in a country’s civil registry. Ethiopia has one of the lowest levels of civil registration in general globally, and of birth registration in particular with only 3 per cent of children under the age 5 registered with civil authorities. In Somali Region of Ethiopia, only 1% of children under 5 have their births registered. A major gap identified in the civil registration system in Ethiopia is the linkage between the health and the civil registration sectors with most children delivered at the health facilities or in the communities not appropriately registered. This case study used qualitative and quantitative methods to describe the process and outcome of a pilot project on improving birth registration using the health system (health facilities and the community health structures) in 2 project woredas (districts) in Somali region of Ethiopia where no birth had been registered more than five years prior the pilot. Within the one-year study period, all 577 births assisted by health extension workers were provided with birth notification slips and 795 (98%) newborns have their birth registered and received birth certificates out of 809 total births reported in the project sites. The study demonstrated the effectiveness of health workers and community structure (mentor mothers) through their community sensitization and mobilization and active reporting process in facilitating registration of births in the civil registration system.